ANALYSIS OF LIQUIDITY RATIO IN MEASURING FINANCIAL PERFORMANCE PT AIR ASIA INDONESIA Tbk - Purba, Arlina (Politeknik Negeri Medan, 2025)
This study aims to determine the financial performance of PT AirAsia Indonesia Tbk through the liquidity ratio for the period 2016-2024. The object of this study is PT AirAsia Indonesia Tbk. The report analyzed is the Financial Position Report of PT AirAsia Indonesia Tbk for the period 2016 to 2024. The data collection technique used is the documentation and literature technique. The data analysis technique used is the liquidity ratio, namely the Current Ratio, Quick Ratio and Cash Ratio. The processed data is then analyzed using Descriptive Analysis. The results of the study indicate that the Liquidity Ratio of PT AirAsia Indonesia Tbk for the period 2016-2024 is measured from the current ratio, quick ratio and cash ratio is in a